Blogs' archives and revision of the past: A case study. (April 2022) - Urban, Palina
In the beginning of the twenty-first century, the personal diary made a transition from its traditional form to the online space. This change of medium transformed the policies of subjectivity which previously structured personal journaling. One of the most profound transformations was the modified relationship of individuals with their past. Former feelings and experiences that did not fit newly constructed biographical storylines used to be discarded, rejected and, ultimately, forgotten. Personal diaries containing the testimonies of undesired past attitudes were often destroyed, but online journals allowed their authors to revisit and remould their past to bring it into alignment with their changing life story. This article presents a case study of a blogger's practice of managing her LiveJournal archive containing biographical texts created over almost two decades. It illustrates how new life-writing technology is employed by bloggers to secure continuity of their autobiographical narrative.